PROSPECTIVE DESCRIPTIVE STUDY OF NON-THYROIDAL NECK SWELLINGS IN WESTERN INDIAN POPULATION - Husain, J.; Rajagopalan, S.; Nair, V. V.; Nagamahendran, R.; Sharma, P.; Roy, N.; Rao, P. P. (International Journal of Medicine and Medical Research, 2023)
Background. Nonthyroidal neck swellings are common and cause diagnostic challenges. This study highlights various diagnosis associated with non-thyroidal neck swellings and their management challenges. Objective. This pilot study highlights the various diagnosis associated with nonthyroidal neck swellings and their management challenges. The clinical spectrum of two most common aetiology of nonthyroidal neck swelling: tubercular cervical lymphadenopathy and lymphomas, are also compared. Methods. This prospective study was conducted in a tertiary care teaching hospital from 01 Jun 2018 to 31 Dec 2019. The first 100 nonthyroidal neck swellings presented to the surgical outpatient department were included and assessed clinically, radiologically and histopathologically. Comparison was carried out between the first two common diagnosis of tubercular cervical lymphadenitis and lymphoma. Continuous variables were analysed using Student’s t-test and categorical data were analysed using the Chi square test. A statistical p value <0.05 was taken as significant. Results. There were 73 lymph node swellings and 27 non-lymph node swellings in the study. The most common diagnosis was tubercular cervical lymphadenitis (n=38) and lymphoma (n=17). The mean volume of lymph nodes in the lymphoma group (38.72±22.12 cm3) was significantly bigger than in the tuberculosis group (9.44±5.99 cm3) P=0.00001. The mean age (33.81±11.8 years) of tubercular patients was significantly less than the lymphoma (52.38±25.3 years) with P=0.000167. The clinical diagnosis was nearly accurate in 85% of cases. However, in 15 cases clinical diagnosis was changed after fine needle aspiration cytology. Conclusions. Ultrasonography and fine needle aspiration cytology are very useful adjunct in arriving at a definite diagnosis of a lymph node swelling in neck. Tubercular cervical lymphadenopathy and lymphoma were two major diagnosis. Tubercular cervical lymphadenopathy is significantly different from lymphomas in terms of early age of presentation and smaller size at the time of presentation.